Crosstalks Between Gut Microbiota and Vibrio Cholerae - Qin, Zixin; Yang, Xiaoman; Chen, Guozhong; Park, Chaiwoo; Liu, Zhi (Frontiers in Cellular and Infection Microbiology, 2020)
Vibrio cholerae, the causative agent of cholera, could proliferate in aquatic environment and infect humans through contaminated food and water. Enormous microorganisms residing in human gastrointestinal tract establishes a special microecological system, which immediately responds to the invasion of V.cholerae, through “colonization resistance” mechanisms, such as antimicrobial peptide production, nutrients competition, and intestinal barrier maintenances. Meanwhile, V.cholerae could quickly sense those signals and modulate the expression of relevant genes to circumvent those stresses during infection, leading to successful colonization on the surface of small intestinal epithelial cells. In this review, we summarized the crosstalks profiles between gut microbiota and V.cholerae in the terms of Type VI Secretion System (T6SS), Quorum Sensing (QS), Reactive Oxygen Species (ROS)/pH stress, and Bioactive metabolites. These mechanisms can also be applied to molecular bacterial pathogenesis of other pathogens in host.